Real-world clinical performance of commercial SARS-CoV-2 rapid antigen tests in suspected COVID-19: A systematic meta-analysis of available data as of November 20, 2020 - Hayer, Johannes; Kasapic, Dusanka; Zemmrich, Claudia (International journal of infectious diseases, 2021)
[Display omitted] •Rapid antigen tests (RATs) can aid diagnosis of SARS-CoV-2 infection.•RAT sensitivity ranged from 28.9% (95% CI 16.4–44.3) to 98.3% (95% CI 91.1–99.7).•RAT specificity ranged from 45% (95% CI 23.1–68.5) to 100% (95% CI 99.7–100).•RAT sensitivity was improved in samples with high viral loads (low Ct).•Data support the use of rapid antigen tests in high-viral-load populations. Rapid antigen tests, or RATs, are a type of lateral flow chromatographic immunoassay utilized to aid the diagnosis of SARS-CoV-2 infection. We performed a systematic meta-analysis to compare the real-world performance of commercially available RATs. We searched several databases and websites for manufacturer-independent prospective clinical performance studies comparing SARS-CoV-2 RATs and RT-PCR. Only studies on RATs that did not need a separate reader for result retrieval and that reported data on viral load, patients’ symptom status, sample type, and PCR assay used were included. 19 studies utilizing 11,109 samples with 2,509 RT-PCR-positives were included. RAT sensitivity varied between 28.9% (95% CI 16.4–44.3) and 98.3% (95% CI 91.1–99.7), likely dependent upon population characteristics, viral load, and symptom status. RAT specificity varied between 92.4% (95% CI 87.4–95.9) and 100% (95% CI 99.7–100) with one outlier. The RATs by Roche Diagnostics/SD Biosensor and Abbott had the highest pooled sensitivity (82.4% [95% CI 74.2–88.4] and 76.9% [95% CI 72.1–81.2], respectively). Sensitivity in high-viral-load samples (cycle threshold ≤25) showed heterogeneity among the different RATs. The RATs offered by Roche Diagnostics/SD Biosensor and Abbott provide sufficient manufacturer-independent, real-world performance data to support their use to detect current SARS-CoV-2 infection, particularly in high-viral-load populations.